2008
DOI: 10.1016/j.ejcts.2008.04.034
|View full text |Cite
|
Sign up to set email alerts
|

Results of an extracardiac pericardial-flap lateral tunnel Fontan operation☆

Abstract: Extracardiac pericardial-flap lateral tunnel Fontan operation is relatively simple and feasible even in patients with previous median sternotomies. The mid-term results were acceptable, and the lateral tunnel demonstrated a tendency to preserve its tubular shape. However in some patients, dilatation of the pericardial-flap tunnel was observed during follow up. Longer follow-up is required to determine the morphologic changes of the lateral tunnel and the value of this technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…An extracardiac LT with pedicled pericardium may become an alternative procedure of LT-TCPC. Some authors have reported that an LT created with pedicled pericardium can grow while also preserving the tubular morphology of the LT and maintaining good haemodynamics [7,8]. However, there has so far been no report regarding the long-term outcome of LTcreated with a pedicled pericardium and which describes its growth in detail.…”
Section: Discussionmentioning
confidence: 96%
“…An extracardiac LT with pedicled pericardium may become an alternative procedure of LT-TCPC. Some authors have reported that an LT created with pedicled pericardium can grow while also preserving the tubular morphology of the LT and maintaining good haemodynamics [7,8]. However, there has so far been no report regarding the long-term outcome of LTcreated with a pedicled pericardium and which describes its growth in detail.…”
Section: Discussionmentioning
confidence: 96%
“…Computer modeling of fluid dynamics of the effects of exercise on hemodynamics of two techniques recently developed have demonstrated the superiority of the external conduit when compared to the lateral tunnel [23]. For this reason, the vast majority of the techniques presented recently in the literature is based on the concept of external conduit [24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%